A dimensão técnico-operativa no exercício profissional dos assistentes sociais nos centros de atendimento socioeducativo de Mato Grosso - Lopes, Vanessa Martins Galhardo (2019)
This dissertation deals with of how the technical-operative dimension in the social workers' professional practice is materialized in the Mato Grosso Socio-Educational Care Centers (CASEs), based on the understanding that this dimension is the closest to professional practice, and, for this reason, it explains the totality of the theoretical-methodological and ethical-political dimensions that constitute the professional exercise, emanating the way of being of the profession and representing the social image and function of Social Work. The interest in this research comes from the experience as a Social Worker working in the SocioEducational System for almost ten years, which allowed us to know the complexities that cross the daily life and that challenge to reaffirm the private attributions, professional actions, as well as the teleological proposal of the Professional Ethical-Political Project in this sociooccupational space. To carry out the analysis and achieve the defined objectives a qualitative descriptive research was developed, using as a primary data source instrument the semistructured interview, conducted with seven Social Workers who work at Mato Grosso CASEs, and as secondary sources public documents and references bibliographic. From the sources used, it was possible to consider, through the analysis, that there are weaknesses regarding the understanding of the technical-operative dimension in the professional exercise, that the challenges and institutional limits impact both the understanding regarding the professional attributions and competences, in the sense of differentiate them from the institutional determinations and the demands of the users, as in the development of the exercise and the professional autonomy, and that it is necessary to look for alternatives to allow the construction of a critical-reflexive look through the permanent education, besides make possible the constitution of strategies for the political and collective organization, the participation in the meetings of the CFESS / CRESS committees, and thus contribute to qualify the professional responses considering the direction of the Ethical-Political Project. Social Work Professional.